A Systematic Review on The Implementation of Game-based Learning to Increase EFL Students’ Motivation - Cahya Susaniari, Ni Kadek Anggi; Santosa, Made Hery (Journal of English Language and Education, 2024)
This systematic literature review examines the effect of implementing game-based learning on increasing student motivation in learning English as a Foreign Language (EFL). By analyzing eleven relevant articles published between 2017 and 2024, this review identifies the effects of implementing game-based learning. Game-based Learning as an effective strategy for increasing English as a Foreign Language (EFL) students' motivation and learning outcomes. The findings show that Game-based Learning significantly increases student motivation, besides that game-based learning can also improve student vocabulary and academic results. Game-based learning has also been shown to reduce anxiety and support collaborative learning, strengthen relationships between students and teachers, and increase student engagement in learning. Further recommendations for future research in the application of game-based learning should focus on optimizing Game-based Learning for various learning contexts, effective types of games, duration of use, and integration with traditional methods, as well as developing training programs for teachers.